Bridging education and global apprenticeship through a work-based learning approach in language and soft-skills training - Viona, Elsa; Danim, Sudarwan; Medriati, Rosane; Kristiawan, Muhammad (Edelweiss Applied Science and Technology, 2026)
This study examines how Bright Education Indonesia (BEI) implements a preparatory work-based learning (WBL) model to prepare Indonesian students for the German Ausbildung program, a dual vocational apprenticeship system in Europe. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis involving trainees, alumni, instructors, and administrators. Thematic analysis was used to document participants’ experiences and perceptions of BEI’s training approach. The findings indicate that BEI combines intensive language training, soft skills development focused on workplace readiness, and cultural orientation into a comprehensive preparatory WBL model. This approach helps learners develop essential communication skills, discipline, adaptability, and collaboration competencies before entering the German apprenticeship system. Alumni reported that this preparatory stage significantly reduced cultural and linguistic barriers and improved their overall readiness for international WBL participation. The study concludes that preparatory WBL models can effectively bridge the gap between domestic training and international apprenticeship systems by addressing both technical and socio-cultural preparedness. The novelty of this research lies in extending the WBL framework beyond direct workplace engagement to include preparatory institutional contexts, demonstrating how training institutions can serve as vital intermediaries in global labor mobility pathways. Practically, the study offers a replicable model for institutions aiming to facilitate student integration into international apprenticeship systems. Theoretically, it contributes to WBL literature by conceptualizing preparatory training as a legitimate and valuable phase within broader work-based learning ecosystems, especially in cross-cultural vocational education contexts.